ANALISIS TANTANGAN DAN STRATEGI E-LEARNING DALAM PEMBELAJARAN (PAI) DI ERA DIGITAL : SYSTEMATIC LITERATURE REVIEW - Rusliana, Zakiyatun Nufus Aulia; Koderi, Koderi; Fitriani, Fitriani (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The development of digital technology and the acceleration of online learning in the post-pandemic era have encouraged the implementation of e-learning in Islamic Religious Education (IRE). However, its implementation still faces a gap between pedagogical potential and practical realities in the field. This study aims to identify the main challenges, recommended e-learning strategies, and the impact of e-learning implementation on students’ understanding of learning materials, learning motivation, and the formation of Islamic character. This research employs a Systematic Literature Review (SLR) method guided by PRISMA, with the assistance of the Covidence application. The review process includes the formulation of three research questions, the determination of inclusion and exclusion criteria, literature searches in the Scopus and Publish or Perish databases, duplicate removal, title–abstract and full-text screening, quality assessment (QA1–QA3), and data synthesis. Out of 198 articles published between 2020 and 2025, 16 articles were deemed eligible for analysis. The findings indicate that e-learning has the potential to enhance students’ understanding of Islamic concepts and learning outcomes through the use of videos, interactive quizzes, and digital materials, as well as to increase students’ motivation and engagement through interactivity and gamification. The main challenges identified include technical aspects, such as limited internet access and infrastructure, and non-technical aspects, such as low digital literacy, insufficient teacher training, student motivation, and policy support. This study emphasizes that the effectiveness of e-learning in IRE can be achieved through the utilization of Learning Management Systems (LMS) enriched with interactive media and gamification, accompanied by the strengthening of teachers’ digital competencies and equitable infrastructure development to ensure sustainable implementation and value-oriented learning. ABSTRAK Perkembangan teknologi digital dan percepatan pembelajaran daring pascapandemi mendorong penerapan e-learning dalam pembelajaran Pendidikan Agama Islam (PAI). Namun, implementasinya masih menghadapi kesenjangan antara potensi pedagogis dan realitas di lapangan. Penelitian ini bertujuan untuk mengidentifikasi tantangan utama, strategi e-learning yang direkomendasikan, serta dampak penerapannya terhadap pemahaman materi, motivasi belajar, dan pembentukan karakter Islami peserta didik. Penelitian menggunakan metode Systematic Literature Review (SLR) berpedoman pada PRISMA dengan bantuan aplikasi Covidence. Proses kajian meliputi perumusan tiga research questions, penetapan kriteria inklusi dan eksklusi, penelusuran literatur pada basis data Scopus dan Publish or Perish, penghapusan duplikasi, screening judul–abstrak dan full-text, penilaian kualitas (QA1–QA3), serta sintesis data. Dari 198 artikel publikasi periode 2020–2025, sebanyak 16 artikel dinyatakan layak dianalisis. Hasil kajian menunjukkan bahwa e-learning berpotensi meningkatkan pemahaman konsep keislaman dan hasil belajar melalui pemanfaatan video, kuis interaktif, dan materi digital, serta meningkatkan motivasi dan keterlibatan siswa melalui interaktivitas dan gamifikasi. Adapun tantangan utama yang ditemukan meliputi aspek teknis, seperti keterbatasan akses internet dan infrastruktur, serta aspek non-teknis, seperti rendahnya literasi digital, minimnya pelatihan guru, motivasi siswa, dan dukungan kebijakan. Penelitian ini menegaskan bahwa efektivitas e-learning PAI dapat dicapai melalui pemanfaatan Learning Management System (LMS) yang diperkaya media interaktif dan gamifikasi, disertai penguatan kompetensi guru serta pemerataan infrastruktur agar implementasi pembelajaran tetap berkelanjutan dan berorientasi pada nilai-nilai Islam.